Thermochemical and conformational study of optical active phenylbenzazole derivatives. (January 2018) - Silva, Ana L.R.; Matos, M. Agostinha R.; Morais, Victor M.F.; Ribeiro da Silva, Maria D.M.C.
Graphical abstract: Highlights: Combustion enthalpies for four phenylbenzazole derivatives have been determined by combustion calorimetry. Enthalpies of sublimation of four phenylbenzazole derivatives have been measured by Calvet microcalorimetry. Vapour pressure dependence with the temperature for 2-(2-hydroxyphenyl)benzoxazole studied by Knudsen effusion method. Intramolecular hydrogen bond energy was derived for three 2-(2-hydroxyphenyl)benzazoles. Gas-phase enthalpies of formation for five phenylbenzazole derivatives were estimated from G3(MP2)//B3LYP approach. Abstract: The energetic study of 2-phenylbenzoxazole (PBO), 2-phenylbenzothiazole (PBT), 2-(2-hydroxyphenyl)benzoxazole (HBO) and 2-(2-hydroxyphenyl)benzothiazole (HBT) has been developed either using experimental techniques or computational calculations. The enthalpies of combustion and of sublimation of these compounds were determined and the gas-phase standard molar enthalpies of formation were derived. The experimental techniques used were static or rotating bomb combustion calorimetry, high temperature Calvet microcalorimetry and/or the Knudsen-effusion method. Additionally, we have obtained the gas-phase standard molar enthalpies of formation of these compounds, as well of 2-(2-hydroxyphenyl)benzimidazole (HBI), through high level ab initio calculations, at the G3(MP2)//B3LYP level. The computational study of the molecular structures of all these compounds has been carried out and four possible conformers were observed for the molecules of each compound, where the keto tautomers have always higher energy than the enol forms. Furthermore, the energetic effects associated to the presence of the hydroxyl group on the core of the 2-phenylbenzazole rings, in particular the hydrogen bond network, were also evaluated.